It is currently 20 Nov 2017, 12:36

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# a, b, c are integers. Is their product abc equal to 0? 1.

Author Message
Intern
Joined: 03 Feb 2007
Posts: 31

Kudos [?]: 10 [0], given: 0

a, b, c are integers. Is their product abc equal to 0? 1. [#permalink]

### Show Tags

25 Sep 2007, 08:17
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

### HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

a, b, c are integers. Is their product abc equal to 0?

1. a^2 = 2a

2. b/c = [(a+b)^2/(a^2 + 2ab + b^2)] - 1

A. Statement (1) ALONE is sufficient, but Statement (2) alone is not sufficient.
B. Statement (2) ALONE is sufficient, but Statement (1) alone is not sufficient.
C. BOTH statements TOGETHER are sufficient, but NEITHER statement ALONE is sufficient.
D. EACH statement ALONE is sufficient.
E. Statements (1) and (2) TOGETHER are NOT sufficient.

Kudos [?]: 10 [0], given: 0

Intern
Joined: 02 Aug 2007
Posts: 36

Kudos [?]: 43 [0], given: 0

### Show Tags

25 Sep 2007, 08:26
Parbe wrote:
a, b, c are integers. Is their product abc equal to 0?

1. a^2 = 2a

2. b/c = [(a+b)^2/(a^2 + 2ab + b^2)] - 1

A. Statement (1) ALONE is sufficient, but Statement (2) alone is not sufficient.
B. Statement (2) ALONE is sufficient, but Statement (1) alone is not sufficient.
C. BOTH statements TOGETHER are sufficient, but NEITHER statement ALONE is sufficient.
D. EACH statement ALONE is sufficient.
E. Statements (1) and (2) TOGETHER are NOT sufficient.

Hi,

Statement 1 alone is not sufficient because (a) could be equal to zero or not. We also do not know about (b) and (c).

In statement 2 note that (a^2 + 2ab + b^2) = (a+b)^2
which makes [(a+b)^2/(a^2 + 2ab + b^2)] - 1 = 1 - 1 = 0
so we know now that b/c = 0. Since a,b,c are integers we conclude that b=0.

Thus Statement 2 alone is sufficient.

Kudos [?]: 43 [0], given: 0

Intern
Joined: 28 Nov 2005
Posts: 33

Kudos [?]: [0], given: 0

### Show Tags

25 Sep 2007, 12:43
I would say answer is B.

Since to hold true B/C = 0 ; B =0

Kudos [?]: [0], given: 0

VP
Joined: 09 Jul 2007
Posts: 1098

Kudos [?]: 144 [0], given: 0

Location: London

### Show Tags

25 Sep 2007, 15:06
Parbe wrote:
a, b, c are integers. Is their product abc equal to 0?

1. a^2 = 2a

2. b/c = [(a+b)^2/(a^2 + 2ab + b^2)] - 1

A. Statement (1) ALONE is sufficient, but Statement (2) alone is not sufficient.
B. Statement (2) ALONE is sufficient, but Statement (1) alone is not sufficient.
C. BOTH statements TOGETHER are sufficient, but NEITHER statement ALONE is sufficient.
D. EACH statement ALONE is sufficient.
E. Statements (1) and (2) TOGETHER are NOT sufficient.

I could not figure out anything to make the answer E. it is B.

Kudos [?]: 144 [0], given: 0

VP
Joined: 10 Jun 2007
Posts: 1434

Kudos [?]: 370 [0], given: 0

### Show Tags

25 Sep 2007, 15:23
Parbe wrote:
a, b, c are integers. Is their product abc equal to 0?

1. a^2 = 2a

2. b/c = [(a+b)^2/(a^2 + 2ab + b^2)] - 1

A. Statement (1) ALONE is sufficient, but Statement (2) alone is not sufficient.
B. Statement (2) ALONE is sufficient, but Statement (1) alone is not sufficient.
C. BOTH statements TOGETHER are sufficient, but NEITHER statement ALONE is sufficient.
D. EACH statement ALONE is sufficient.
E. Statements (1) and (2) TOGETHER are NOT sufficient.

E.

(1) a can be 0 or 2
INSUFFICIENT

(2) b/c = [(a+b)^2/(a^2 + 2ab + b^2)] - 1
=> b = c*[(a+b)^2/(a^2 + 2ab + b^2)] - c
=> b+c = c*[(a+b)^2/(a+b)^2]
=> (a+b)^2 * (b+c) = c*(a+b)^2
=> (a+b)^2 * (b+c) - c*(a+b)^2 = 0
=> ((a+b)^2) * (b) = 0
This gives b=0 or a=-b
INSUFFICIENT

Together, if a=0, then b=0
if a=2, then b=-2
INSUFFICIENT since we don't know c.

Kudos [?]: 370 [0], given: 0

CEO
Joined: 29 Mar 2007
Posts: 2553

Kudos [?]: 528 [0], given: 0

### Show Tags

25 Sep 2007, 16:31
This has to be E.

S1: a could be 2 or 0 insuff.

S2: b/c (when worked out) = 0 (not -1 as I originally posted)

anyway its still insuff.

Last edited by GMATBLACKBELT on 25 Sep 2007, 18:53, edited 1 time in total.

Kudos [?]: 528 [0], given: 0

GMAT Club Legend
Joined: 07 Jul 2004
Posts: 5032

Kudos [?]: 453 [0], given: 0

Location: Singapore

### Show Tags

25 Sep 2007, 19:00
St1:
Could be a = 0, a = 2. Insufficient.

St2:
b/c = [(a+b)^2/(a+b)^2] - 1
b/c = 0

So b = 0. a*b*c = 0.
Sufficient.

Ans B

Kudos [?]: 453 [0], given: 0

Senior Manager
Joined: 13 Mar 2007
Posts: 293

Kudos [?]: 58 [0], given: 0

Location: Russia, Moscow

### Show Tags

26 Sep 2007, 06:42
Parbe wrote:
a, b, c are integers. Is their product abc equal to 0?

1. a^2 = 2a

2. b/c = [(a+b)^2/(a^2 + 2ab + b^2)] - 1

A. Statement (1) ALONE is sufficient, but Statement (2) alone is not sufficient.
B. Statement (2) ALONE is sufficient, but Statement (1) alone is not sufficient.
C. BOTH statements TOGETHER are sufficient, but NEITHER statement ALONE is sufficient.
D. EACH statement ALONE is sufficient.
E. Statements (1) and (2) TOGETHER are NOT sufficient.

It's E
1) a=0 or a=2 => insufficient
2) b/c=0 (or b=0) only if (a+b) does not equal to 0 (a does not equal to -b), since we know nothing about a => insufficient
1&2) if a=0 and b=0 we forbid the statement that a should not equal to -b
so insufficient

Kudos [?]: 58 [0], given: 0

Director
Joined: 11 Jun 2007
Posts: 909

Kudos [?]: 292 [0], given: 0

### Show Tags

26 Sep 2007, 07:45
this was tricky one.. i fell for the trap and had B at first. thanks for the good explanation

Kudos [?]: 292 [0], given: 0

Manager
Joined: 13 Feb 2007
Posts: 63

Kudos [?]: 1 [0], given: 0

### Show Tags

26 Sep 2007, 09:03
I don't know how anyone could think the answer is e.

statement 1: a = 0, 2. insufficient

statement 2: b = 0. if be = 0, the answer is yes a * b * c = 0

The answer is B very obviously.

Kudos [?]: 1 [0], given: 0

SVP
Joined: 28 Dec 2005
Posts: 1543

Kudos [?]: 185 [0], given: 2

### Show Tags

26 Sep 2007, 18:09
I say B.

St. 1 just tells us that a=2 or -2. Nothing bout b or c, so insufficient

St. 2 tells us that b/c = 1-1 =0 . Therefore, b must equal 0. And any product where one of the terms is 0 makes the overall product 0 .

So , statement 2 seems to be enough, and thats what got me to B

Kudos [?]: 185 [0], given: 2

26 Sep 2007, 18:09
Display posts from previous: Sort by